Dynamic Geometry: P76

Geometry Level pending

The diagram shows a black semicircle with radius 1 1 . The cyan and the green semicircles are tangent to each other and internally tangent to the black semicircle. They are growing and shrinking freely so that the sum of their radius is always equal to 1 1 . We inscribe a purple semicircle so that it's tangent to all three semicircles. When the radius of the purple semicircle is equal to 56 121 \dfrac{56}{121} , the sum of the areas of the cyan and green semicircles can be expressed as p q π \dfrac{p}{q}\pi , where p p and q q are coprime positive integers. Find p + q p+q .


The answer is 307.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 16, 2021

Let the centers of the unit, cyan, green, and purple semicircles be O O , A A , B B , and C C , their radii 1 1 , r 1 r_1 , r 2 r_2 , and r r , Then r 1 + r 2 = 1 r_1 + r_2 = 1 , O A = 1 r 1 = r 2 OA = 1-r_1 = r_2 , and O B = 1 r 2 = r 1 OB = 1-r_2 = r_1 .

Let diameters D E DE and F G FG through centers C C and O O respectively. By intersecting chords theorem ,

D C C E = F C C G r 2 = ( 1 k ) ( 1 + k ) = 1 k 2 k 2 = 1 r 2 \begin{aligned} DC\cdot CE & = FC \cdot CG \\ r^2 & = (1-k)(1+k) = 1 - k^2 \\ \implies k^2 & = 1 - r^2 \end{aligned}

Let C O B = θ \angle COB = \theta . By cosine rule ,

{ B C 2 = O B 2 + O C 2 2 O B O C cos θ C A 2 = O A 2 + O C 2 + 2 O A O C cos θ { ( r 2 + r ) 2 = r 1 2 + ( 1 r 2 ) 2 r 1 1 r 2 cos θ . . . ( 1 ) ( r 1 + r ) 2 = r 2 2 + ( 1 r 2 ) + 2 r 2 1 r 2 cos θ . . . ( 2 ) r 2 × ( 1 ) + r 1 × ( 2 ) : r 1 3 + r 2 3 + 2 ( r 1 2 + r 2 2 ) r + ( r 1 + r 2 ) r 2 = r 1 r 2 ( r 1 + r 2 ) + ( r 1 + r 2 ) ( 1 r 2 ) ( r 1 + r 2 ) ( ( r 1 + r 2 ) 2 3 r 1 r 2 ) + 2 ( ( r 1 + r 2 ) 2 2 r 1 r 2 ) r + r 2 = r 1 r 2 + 1 r 2 Note that r 1 + r 2 = 1 1 3 r 1 r 2 + 2 r 4 r 1 r 2 r + r 2 = r 1 r 2 + 1 r 2 r + r 2 = 2 r 1 r 2 + 2 r 1 r 2 r r = 2 r 1 r 2 \begin{cases} BC^2 = OB^2 + OC^2 - 2 \cdot OB \cdot OC \cdot \cos \theta \\ CA^2 = OA^2 + OC^2 + 2 \cdot OA \cdot OC \cdot \cos \theta \end{cases} \\ \begin{cases} (r_2+r)^2 = r_1^2 + (1-r^2) - 2r_1\sqrt{1-r^2} \cos \theta & ...(1) \\ (r_1+r)^2 = r_2^2 + (1-r^2) + 2r_2\sqrt{1-r^2} \cos \theta & ...(2) \end{cases} \\ \begin{aligned} r_2 \times (1) + r_1 \times (2): \quad r_1^3+r_2^3 + 2(r_1^2+r_2^2)r + \blue{(r_1+r_2)} r^2 & = r_1r_2 \blue{(r_1+r_2)} +\blue{(r_1+r_2)}(1-r^2) \\ \blue{(r_1+r_2)}(\blue{(r_1+r_2)}^2-3r_1r_2) + 2(\blue{(r_1+r_2)}^2 - 2r_1r_2)r + r^2 & = r_1r_2 + 1 - r^2 \quad \quad \small \blue{\text{Note that }r_1+r_2 = 1} \\ 1 - 3r_1r_2 + 2r - 4r_1r_2r + r^2 & = r_1r_2 + 1 - r^2 \\ r + r^2 & = 2r_1r_2 + 2r_1r_2r \\ \implies r & = 2r_1r_2 \end{aligned}

Putting r = 56 121 r = \dfrac {56}{121} , then we have:

2 r 1 r 2 = 56 121 Note that r 2 = 1 r 1 r 1 ( 1 r 1 ) = 28 121 121 r 1 2 121 r 1 + 28 = 0 ( 11 r 1 4 ) ( 11 r 1 7 ) = 0 Since r 1 and r 2 are interchangeable, r 1 , r 2 = 4 11 , 7 11 \begin{aligned} 2r_1r_2 & = \frac {56}{121} & \small \blue{\text{Note that }r_2 = 1-r_1} \\ r_1 (1-r_1) & = \frac {28}{121} \\ 121 r_1^2 - 121r_1 + 28 & = 0 \\ (11r_1 - 4)(11r_1 - 7) & = 0 & \small \blue{\text{Since }r_1 \text{ and }r_2 \text{ are interchangeable,}} \\ \implies r_1, r_2 & = \frac 4{11}, \frac 7{11} \end{aligned}

Then the sum of areas of the cyan and green semicircles π 2 ( ( 4 11 ) 2 + ( 7 11 ) 2 ) = 65 242 \dfrac \pi 2 \left(\left(\dfrac 4{11}\right)^2 + \left(\dfrac 7{11} \right)^2 \right) = \dfrac {65}{242} . Therefore p + q = 65 + 242 = 307 p+q = 65+242 = \boxed{307} .

Thank you sir.

Valentin Duringer - 2 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...